THE EQUALIZATION OF PERIODIC VAT RETURN AND ANNUAL TAX RETURN OF CV. LAJ FOR THE YEAR OF 2020 - Lukman, Elvini; Widjaja, Purnamawati Helen (Graduate Program of Universitas Tarumanagara, 2023)
This research has several purposes, namely to discover the factors that cause difference in the value of gross income reported in Periodic Value Added Tax Return and Annual Tax Return as well as to find out how to perform equalization process to Periodic Value Added Tax Return and Annual Tax Return. This study uses a qualitative descriptive research approach to CV. LAJ, corporate taxpayer who is the subject of this research. With the aim of obtaining data needed in this research, the methods used by the researcher include natural observation, interviews, and documentation studies. The outcomes of the equalization process indicate that the difference in the value of gross income is caused by other operating income transactions, other operating expenses, bonuses, sale discounts, sale returns, claim compensation and cancellation or replacement of output tax invoices.